2017
DOI: 10.1021/acsomega.7b01226
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Properties of Vanadium Diselenide: A Comprehensive Study on Its Electrocatalytic Performance in Alkaline, Neutral, and Acidic Media

Abstract: Here, we report the synthesis of vanadium diselenide (VSe 2 ) three-dimensional nanoparticles (NPs) and two-dimensional (2D) nanosheets (NSs) utilizing nanosecond pulsed laser ablation technique followed by liquid-phase exfoliation. Furthermore, a systematic study has been conducted on the effect of NP and NS morphologies of VSe 2 in their catalytic activities toward oxygen reduction reaction (ORR), oxygen evolution reaction (OER) and hydrogen evolution reaction (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 80 publications
(142 reference statements)
0
41
0
Order By: Relevance
“…Despite the better catalytic activity of these catalysts, their high cost, scarcity, and poor stability limit their commercial and widespread use. Therefore, enormous efforts have been devoted to replacing these catalysts with non‐noble‐metal‐based, abundant, and highly efficient electrocatalysts for water splitting such as VSe 2 , Co oxide, and Fe oxide . The challenge of using such non‐noble‐metal catalysts for water splitting in an alkaline solution is their instability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the better catalytic activity of these catalysts, their high cost, scarcity, and poor stability limit their commercial and widespread use. Therefore, enormous efforts have been devoted to replacing these catalysts with non‐noble‐metal‐based, abundant, and highly efficient electrocatalysts for water splitting such as VSe 2 , Co oxide, and Fe oxide . The challenge of using such non‐noble‐metal catalysts for water splitting in an alkaline solution is their instability.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Despite the better catalytic activity of thesec atalysts, their high cost, scarcity, and poor stability limit their commercial and widespread use. Therefore, enormous efforts have been devotedt or eplacing these catalysts with non-noble-metalbased, abundant, and highly efficient electrocatalysts for water splitting such as VSe 2 , [3] Co oxide, [4,5] and Fe oxide. [6] The challenge of using such non-noble-metal catalysts for water splitting in an alkaline solutioni st heir instability.N ih as as imilar binding energy with hydrogena sP t [7,8] and has been widely considered and applieda sawater-splitting catalysti nv arious forms such as sea-urchin-shaped Ni 3 (VO 4 ) 2 , [9] bimetallic NiMoN nanowires, [10] and Ni 3 Se 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the extra-high electrical conductivity of a VSe 2 monolayer (that has been experimentally proved recently [47]), some other unexpected properties of this material have also been investigated in recent years. Its unique charge density wave (CDW) [50], ferromagnetism behavior [51][52][53], and electrochemical activity [toward a hydrogen evolution reaction (HER)] [54][55][56][57][58] are examples of these explorations. Owing to its metallic nature with no optical band gap, it has been expected that it should not be considered for optical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Image of catalysis, fuel cell: Reproduced with permission. [ 139 ] Copyright 2017, American Chemical Society. Image of cancer theranostics: Reproduced with permission.…”
Section: Advanced Applications Of Vx2mentioning
confidence: 99%
“…[ 136,137 ] Similarly, HER activities of 2D VSe 2 nanosheets are reported, which is summarized in Table 6. [ 63,69,138–140 ] A comparative experimental and DFT studies of VX 2 revealed that VTe 2 emerge as the best performing material for HER with overpotential at 0.5 V versus RHE and Tafel slope of 55 mV dec −1 with an order as VS 2 < VSe 2 < VTe 2 . [ 52 ]…”
Section: Advanced Applications Of Vx2mentioning
confidence: 99%